THE IMPORTANCE OF MODERN COMPUTER TECHNOLOGIES AND ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS AND TREATMENT OF DIABETES MELLITUS - Atahanov Sanjarbek Anvarovich (Modern American Journals, 2025)
This article analyzes the role of modern computer technologies and artificial intelligence in the diagnosis and treatment of diabetes mellitus. The study examines the effectiveness of data analysis and machine learning methods – particularly Random Forest, CNN, and LSTM algorithms – in improving diagnostic accuracy. The Random Forest model achieved 90% accuracy, while CNN demonstrated 93–95% sensitivity in detecting diabetic retinopathy. A literature review shows that AI technologies significantly enhance early diagnosis and glucose monitoring on an international scale. In Uzbekistan, however, developing data infrastructure and clinical validation systems remains necessary for implementing these approaches. The results confirm that artificial intelligence plays a crucial role in early diabetes detection and improving the efficiency of healthcare systems.
Keywords: Diabetes mellitus, artificial intelligence, machine learning, CNN, Random Forest, diagnostics.